Development of the PERISAI Program (Prevention of Sexual Violence and Intimidations) as an Effort to Prevent Gender-Based Violence - Nurhayati Nurhayati; Budi Susetyo; Iding Tarsidi; Muhammad Rijaal Qurrota A'yuni; Ahsen Yılmaz (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
Gender-based violence remains a significant issue in educational settings, including special schools that serve students with special needs. Students in special schools are particularly vulnerable to bullying, intimidation, and sexual violence due to limited self-protection skills, psychosocial challenges, and insufficient preventive support systems. Based on the 2024 Education Report data at State Special School 02 in Serang City, indicators related to bullying and sexual violence were categorized as unsafe, indicating the urgent need for a systematic prevention program. This study aimed to develop the PERISAI Program (Prevention of Sexual Violence and Intimidation) as a collaborative and contextual model for preventing gender-based violence in special schools. This study employed a modified Research and Development (R&D) approach consisting of needs analysis, program design, expert validation, revision, and limited field trials. The participants involved students with special needs, teachers, school counselors, parents, and expert validators. Data were collected through interviews, observations, questionnaires, documentation, and validation sheets, and analyzed using qualitative descriptive analysis and simple quantitative descriptive statistics. The findings revealed that the PERISAI Program was categorized as feasible to highly feasible based on expert validation results. The program was positively received by teachers and parents because it provided practical guidelines for preventing sexual violence and bullying in special school environments. The program integrates prevention education, parental involvement, school support systems, and continuous monitoring within a collaborative framework adapted to the characteristics of students with special needs. This study contributes to the development of a contextual and applicable gender-based violence prevention model for special schools, particularly in educational settings with limited resources and socioeconomically vulnerable families. The PERISAI Program also offers practical implications for strengthening child protection and creating safer and more inclusive educational environments.